Premature ejaculation in urban Malaysian population: the associations between erectile dysfunction (ED), anxiety and depression - Arasalingam, Shamini; Sidi, Hatta; Ng, Chong Guan; Das, Srijit; Midin, Marhani; Musa, Ramli (Faculty of Medicine, International Islamic University Malaysia, 2016)
Introduction: Both premature ejaculation(PE) and erectile dysfunction(ED) are prevalent sexual health disorders that have been inadequately investigated in Malaysia, a multiethnic and conservative nation.The objective of the study was to study the relationship between PE and ED, and other common mental health issues, i.e. anxiety and depression in Malaysian urban population. Methods: The diagnosis for PE was established by clinical diagnosis using DSM-5 and ISSM definition criteria for PE, whereas a diagnosis of ED was established by the International Index of Erectile Function (IIEF) questionnaire. Anxiety and depression levels were detected from the Hospital Anxiety and Depression Scale (HADS). Results: Based on DSM-V and ISSM clinical diagnosis for PE, the prevalence of PE was found to be 25%. Erectile dysfunction (p = 0.035, OR = 3.315, 95% CI 1.088, 10.103) and severe anxiety (p = 0.020, OR = 7.656, 95% CI 1.383, 42.396) significantly predicted presence of PE. Conclusion: There was a strong association between PE and ED and between PE and anxiety. Routine examination for PE in male patients should address the issue and the management of both ED and anxiety among PE patients, especially in an urban Malaysian clinical and medical care setting.